Analysis of the Quality of Bottled Drinking Water Products through a Six Sigma Approach and Failure Mode and Effect Analysis (FMEA): (Case Studies: PT XYZ) - Fimahali, Ahmad Yusuf; Sumiati, Sumiati (PT Mattawang Mediatama Solution, 2023)
PT XYZ is a company engaged in Bottled Drinking Water (AMDK) with the brand